Laser Raman spectroscopy with different excitation sources and extension to surface enhanced raman spectroscopy - Wahadoszamen, Md; Haider, A F M Yusuf; Rahaman, Arifur; Hoque, Nabil Md. Rakinul; Talukder, Aminul I; Abedin, Kazi Monowar (© 2015 Hindawi Publishing Corporation, 2017)
This article was published in the Journal of Spectroscopy [© 2015 Hindawi Publishing Corporation] and the definite version is available at : 10.1155/2015/895317